Ansible Quick Start Guide : Control and Monitor Infrastructures of Any Size, Physical or Virtual. - Alibi, Mohamed (Birmingham : Packt Publishing Ltd, 2018)
Configuration Management (CM) tools help administrators reduce their workload. Ansible is one of the best Configuration Management tools, and can act as an orchestrator for managing other CMs. This book is the easiest way to learn how to use Ansible as an orchestrator and a Configuration Management tool. With this book, you'll learn how to ...
Firewall UFW management moduleHAProxy control module; Wake-on-LAN trigger module; Linux storage modules; File system management module; Device mounting module ; Disk partitioning module; GlusterFS control module; Ansible Windows modules; Windows System Modules; Windows user and group management module; Windows register editing module; Windows service management module; Windows updates and feature management modules (win_updates, win_hotfix, and win_feature); Windows Wake-on-LAN trigger module; Windows firewall management module; Windows package modules; Chocolatey control module.
Print version record.
Windows package manager.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Application software -- Development; Logiciels d'application -- Développement.; Computer networking & communications; Computer architecture & logic design; Computers -- Systems Architecture -- General; Computers -- System Administration -- Linux & UNIX Administration; Computers -- System Administration -- General; Application software -- Development; Electronic book